Clinical benefits of enhanced 3D-NEVERview sequence in MRI simulation for nasopharyngeal carcinoma patients received radiotherapy - Yuanyuan Li; Yin Zhang; Ran Tang; Anyan Gu; Zhenyu Pan; Guozi Yang; Yaotao Li; Yu Wu; Zhuocheng Li; Lixiang Yang; Zhitao Dai; Xingru Sun (BMC Cancer)
Abstract Background and purpose To test whether the enhanced 3D-NEVERview (3D-NEVERview + C) sequence improves delineation accuracy and allows clinically meaningful dose reductions to the brachial plexus of nasopharyngeal carcinoma (NPC) with cervical lymph node metastasis in radiotherapy during MRI simulation. Materials and methods Fifty NPC patients with cervical lymph node metastasis were enrolled. The contrast-to-noise ratio (CNR), signal-to-noise ratio (SNR), and contrast ratio (CR) of brachial plexus were compared between two different sequences. The volumes of brachial plexus delineated automatically (Vauto−L, Vauto−R) and manually (VBP−L, VBP−R) were performed statistical comparisons. Radiotherapy plans were categorized into original plans (without dose constraints on the brachial plexus) and optimized plans (with dose constraints). The volumes receiving 60 Gy (V60) and 66 Gy (V66), maximum dose (Dmax) and mean dose (Dmean) to brachial plexus were analyzed statistically. Results CNR, SNR, and CR between two sequences showed statistical significance (P < 0.05). The volumes of Vauto−L, Vauto−R, VBP−L and VBP−R were (2.38 ± 0.78) cm³, (2.40 ± 0.87) cm³, (27.07 ± 5.32) cm³ and (27.00 ± 5.74) cm³, respectively, with significant differences (P < 0.001). The V60 and V66, Dmax and Dmean of brachial plexus also differed significantly between the original and optimized plans (P < 0.05). Conclusion The 3D-NEVERview + C sequence significantly enhances the CR, thereby providing a clearer location of brachial plexus. In NPC patients with cervical lymph node metastasis, excessive doses to brachial plexus frequently occurred. Protecting brachial plexus during radiotherapy is crucial for reducing the risk of nerve injury. Therefore, incorporating the 3D-NEVERview + C sequence in MRI-sim is highly recommended.